1988
DOI: 10.1677/jme.0.001r001
|View full text |Cite
|
Sign up to set email alerts
|

Esta: A Bioassay System for the Determination of the Potencies of Hormones and Antibodies Which Mimic Their Action.

Abstract: A bioassay system named ESTA (eluted stain assay) has been developed to measure hormones and antibodies which mimic their action. It is derived from approaches used for cytochemical bioassays. Unlike the latter which use tissue segments or sections, ESTA is based upon uniform microcultures of target cells maintained in microtitre plates. Direct elution of the cytochemical stain from these microcultures into the wells of the microtitre plates permits rapid quantification with a microtitre plate reader. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Thus, exposure of small pieces of mouse epidermis, trachea, esophagus, tongue, liver, and cardiac muscle to LCM-EGTA for up to 6 h did not disrupt desmosome adhesion, as shown by transmission electron microscopy, even though separation of the cell membranes and vacuolation of cells indicated that the tissues were clearly affected by calcium removal (Figure 3). Parallel immunofluorescence studies indicated that E-cadherin in tissues was internalized during the exposure to LCM-EGTA (our unpublished results), and 3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyltetrazolium bromide assay (Ealey et al, 1988) showed that the tissues remained viable after this treatment.…”
Section: The Calcium Dependence Of Desmosomes Changes With Time In Cementioning
confidence: 54%
“…Thus, exposure of small pieces of mouse epidermis, trachea, esophagus, tongue, liver, and cardiac muscle to LCM-EGTA for up to 6 h did not disrupt desmosome adhesion, as shown by transmission electron microscopy, even though separation of the cell membranes and vacuolation of cells indicated that the tissues were clearly affected by calcium removal (Figure 3). Parallel immunofluorescence studies indicated that E-cadherin in tissues was internalized during the exposure to LCM-EGTA (our unpublished results), and 3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyltetrazolium bromide assay (Ealey et al, 1988) showed that the tissues remained viable after this treatment.…”
Section: The Calcium Dependence Of Desmosomes Changes With Time In Cementioning
confidence: 54%
“…The potency of the hormone tion, [12][13][14] local release of this hormone from hormonewas measured with a uniquely precise bioassay which loaded PMMA may promote early postoperative bone is based upon the eluted stain assay system (ESTA) which we recently developed. 18,19 The immunoactivity of the hGH released was also monitored using a con-duced by the incorporation into the methacrylate cedisc weight was generally 5-6%. These weights were used to calculate the weight-corrected percentage rement.…”
Section: Introductionmentioning
confidence: 99%
“…21 They were routinely grown in suspension culThis was followed by careful mixing (10 min) to ensure ture as described previously. 18,19 homogeneity, and finally, the addition of the liquid monomer. The cements were allowed to dough and Bioassay were then cast into discs in PTFE molds (10 mm in diameter and 7 mm deep).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of bioactive hGH were determined using the ESTA bioassav. These detailed studies were possible because of the performance charac teristics of the ESTA bioassay, which has the precision and high sample capacity which is normally only attain able with immuno-or radioligand assay [1][2][3][4][5][6]. The ESTA bioassay is based upon the response of Nb2 rat lymphoma cells to lactogens such as hGH.…”
Section: Introductionmentioning
confidence: 99%